2010
DOI: 10.3340/jkns.2010.47.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Based Stress Reduction Program on Depression, Anxiety and Stress in Patients with Aneurysmal Subarachnoid Hemorrhage

Abstract: Objective : In this study, the Mindfulness Based Stress Reduction (MBSR) program was applied to patients presenting with depression and anxiety after surgery from spontaneous subarachnoid hemorrhage (SAH) and the effects were assessed. Methods : The subjects were patients admitted for cerebral aneurysm rupture and treated by means of surgery from March to December, 2007. More than 6 months had passed after surgery, without any special lesions showing up on computed tomography (CT), and the Glasgow outcome scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 23 publications
4
68
0
1
Order By: Relevance
“…Examples include studies suggesting effectiveness for depressive 78,[176][177][178] as well as anxiety symptoms, [178][179][180][181] including PTSD, 176 social anxiety disorder, 78,182 and generalized anxiety disorder. 183 However, a comparison with group cognitive behavioral therapy (CBT) for social anxiety disorder found that the CBT intervention was more effective than MBSR.…”
Section: Mindfulness-based Stress Reductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Examples include studies suggesting effectiveness for depressive 78,[176][177][178] as well as anxiety symptoms, [178][179][180][181] including PTSD, 176 social anxiety disorder, 78,182 and generalized anxiety disorder. 183 However, a comparison with group cognitive behavioral therapy (CBT) for social anxiety disorder found that the CBT intervention was more effective than MBSR.…”
Section: Mindfulness-based Stress Reductionmentioning
confidence: 98%
“…191,192 Evidence indicates that MBSR improves general mental health, 193 and many studies indicate improved psychological functioning among individuals with a variety of medical disorders. 164,177,178,184,[194][195][196][197][198][199][200] However, MBSR is also effective for healthy people, 181,201 and some evidence indicates that MBSR may be beneficial for psychological functioning among health care professionals. [202][203][204] Although most studies have been conducted with adults, recent research also suggests a benefit for adolescents.…”
Section: Mindfulness-based Stress Reductionmentioning
confidence: 99%
“…Mindfulness-based therapies have proved to be effective in a wide range of physical and psychological problems such as chronic pain (10), depression, anxiety, and stress among college students (11) or people with subarachnoid hemorrhage (12), psychosocial stress (13), and depression (14), as well as distinct psychiatric disorders, including hypochondriasis (15), social phobia (16), generalized anxiety disorder (17), obsessive-compulsive disorders (18), and somatization disorder (19). Mindfulness-based relapse prevention (20) is a program integrating mindfulness meditation practices with traditional relapse prevention (RP).…”
Section: Introductionmentioning
confidence: 99%
“…(2012) found reduced mental fatigue and improved cognitive function (processing speed and attention) after the completion of an MBSR program for participants suffering from mental fatigue after TBI or stroke (Johansson et al, 2012). Other researchers also reported on positive effects after an MBSR course for people who had suffered a TBI with improved quality of life, perceived self-efficacy and cognition (Azulay, Smart, Mott, & Cicerone, 2013), improved quality of life and decreased depression (Bedard and co-workers, 2003), and, after a stroke decreased depression (Joo, Lee, Chung, & Shin, 2010). Fatigue was not included in these studies, but reduced fatigue after MBSR has been reported in other diseases e.g.…”
Section: Mental Fatigue After An Acquired Brain Injurymentioning
confidence: 99%